1960 dönemi Türk Sineması ve toplumsal gerçekçi çalışmalar - Çebi, Zafer (My University, 2006)
1960 DÖNEMİ TÜRK SİNEMASI VE TOPLUMSAL GERÇEKÇİ ÇALIŞMALAR 27 Mayıs 1960’da yaşanan askeri darbe önemli bir değişimin habercisi olmuştur. Bu değişim, en büyük yansımasını ise sinemada bulmuştur. 1960’lı yılların ilk yarısına kadar sinemada etkin olan bu yansıma ‘Toplumsal Gerçekçilik’ adını almıştır. Bu çalışmada; 27 Mayıs askeri darbesinin ardından Türk Sineması’nda belirginlik kazanan ‘Toplumsal Gerçekçilik’ kavramı ele alınmıştır. Kavram, dönemin toplumsal ve siyasal gelişmeleri içinde incelenmiştir. Kavramın sinemada hayat buluşunu ise dönem içerisinde yer alan bazı yönetmen ve filmler üzerinden anlatılmıştır.

TURKISH MOVIE SECTOR AND THE SOCIAL REALISTIC STUDIES DURING 1960s The army takeover on May 27, 1960 proved a changed news with respect to its future consequences. One of the most critical reflections of this change was experienced in movies which was effective especially in the first half of 1960s and its known as “Social Realism”. In this thesis; the concept of “Social Realism” have been taken under consideration as a prominent character of the Turkish movie sector after May 27. This concept has been examined considering the social and political developments of that period. The development of this concept has been narrated by focusing on the directors, who experienced this period, and movies made in that era.
Keywords: Sanat ve Toplum; Sinema, Türk